Efforts To Prevent the Transmission of COVID-19 Through Empowerment of MTS Amaliyah School Teachers About the 5m COVID-19 Movement in Facing Offline Learning for Academic Year 2021/2022 - Nurbaiti; Darti, Nur Afi; Siregar, Farida Linda Sari; Ariadni, Dwi Karina (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The rise of Covid 19 cases during this pandemic has compelled the government to implement various strategies and rules that the entire community must adhere to. Griffith University Australia (2020), Indonesia should no longer apply the 3M health protocol as a step to anticipate the spread of Covid 19. The increased number cases in Indonesia forces the implementation of 5M health protocol to prevent the spread of Covid 19, which includes washing hands with soap and running water, wearing masks, maintaining physical distance, avoiding crowds, and limiting mobility, in accordance with the regulation of the Minister of Health. The start of 2021 offline learning in July becomes one of the major challenges that compels teachers to be familiar with this regulation. Therefore, various direct strategies to people are required in order to increase their knowledge and understanding. The objective of this community service is to increase the understanding and capacity of the teachers and all education personnel of MTs (Islamic Junior High School) Amaliyah to prevent the spread of Covid 19 by implementing the 5M health protocol, as well as assisting the provision of offline learning preparation tools such as masks, gloves, hand soap, disinfectants, social distancing stickers, and portable hand-washing stations.